Chronic social stress induces DNA methylation changes at an evolutionary conserved intergenic region in chromosome X. Issue 6 (3rd June 2018) - Hing, Benjamin; Braun, Patricia; Cordner, Zachary A.; Ewald, Erin R.; Moody, Laura; McKane, Melissa; Willour, Virginia L.; Tamashiro, Kellie L.; Potash, James B.
ABSTRACT: Chronic stress resulting from prolonged exposure to negative life events increases the risk of mood and anxiety disorders. Although chronic stress can change gene expression relevant for behavior, molecular regulators of this change have not been fully determined. One process that could play a role is DNA methylation, an epigenetic process whereby a methyl group is added onto nucleotides, predominantly cytosine in the CpG context, and which can be induced by chronic stress. It is unknown to what extent chronic social defeat, a model of human social stress, influences DNA methylation patterns across the genome. Our study addressed this question by using a targeted-capture approach called Methyl-Seq to investigate DNA methylation patterns of the dentate gyrus at putative regulatory regions across the mouse genome from mice exposed to 14 days of social defeat. Findings were replicated in independent cohorts by bisulfite-pyrosequencing. Two differentially methylated regions (DMRs) were identified. One DMR was located at intron 9 of Drosha, and it showed reduced methylation in stressed mice. This observation replicated in one of two independent cohorts. A second DMR was identified at an intergenic region of chromosome X, and methylation in this region was increased in stressed mice. This methylation difference replicated in two independent cohorts and in Major Depressive Disorder (MDD) postmortem brains. These results highlight a region not previously known to be differentially methylated by chronic social defeat stress and which may be involved in MDD.